Theater and Actor Training Processes as a Means of Education in the Pandemic - Arif Hidajad (International Conference on Science, Education, and Technology, 2021)
Corona is not known when the incubation period ends, even at the end a new variant emerged from the adaptation of these bacteria to the environment. The period of activity restriction is carried out to prevent the transmission and re-spread of the coronavirus. The status of the pandemic has not yet shown a bright spot towards its normal state. Victims fall with symptoms that are still palpable to this day, the effectiveness of the use of vaccines is competing with the rapid adaptation of the virus. However, when viewed randomly, corona will attack anyone who has a weak immune system. Anxiety and feeling threatened make people experience extreme anxiety. Anxiety and suspicion of people around them make people depressed. Depression and feeling uncomfortable is one of the contributors to the decline in the body's immunity in humans. The body exercise method as a detox, vocal exercise as psychological therapy, and concentration as a self-calming medium are tools that can be used as a process of increasing body immunity. How can drama training tutorial media patterns function as an increase in body immunity? A qualitative descriptive approach with data collection from multi disciplines will be used as a tool to analyze it. An actor's capital is his body, mind and vocals, there is a side that is rarely touched by the benefits of this process in both physical and mental health. Under conditions of stress and depression, humans will find it difficult to produce endorphins in their bodies because there is no communication stimulus in their bodies. In acting training, the body becomes a detoxifier and vocal exercises lighten the burden of one's mind, while concentration becomes a meditative medium in calming oneself. Therefore, the method of acting training needs to be introduced as a medium towards physical and psychological health in order to increase body immunity. Data obtained from interviews, literature, and analysis are adjusted to the object of research. Triangulation of sources and techniques is used to maintain the degree of data actualization and data validity.